Risk factors for multidrug‐resistant tuberculosis in northwest Ethiopia: A case–control study. Issue 4 (15th April 2019) - Alene, Kefyalew Addis; Viney, Kerri; McBryde, Emma S.; Gray, Darren J.; Melku, Mulugeta; Clements, Archie C. A.
Abstract: Ethiopia is one of 30‐high burden multidrug‐resistant tuberculosis (MDR‐TB) countries globally. The aim of this study was to describe the characteristics of patients with MDR‐TB and to investigate risk factors for MDR‐TB relative to having drug‐susceptible tuberculosis (TB), in northwest Ethiopia. A hospital‐based, unmatched case–control study was conducted. Cases were all MDR‐TB patients (i.e., resistant to at least rifampicin and isoniazid) who were confirmed by culture and drug‐susceptibility testing whilst enrolled on treatment at Gondar University Hospital. Controls were all drug‐susceptible tuberculosis (DS‐TB) patients who were confirmed by Gene Xpert MTB/RIF at Gondar University Hospital. Univariable and multivariable logistic regression models were used for comparisons, and odds ratios with 95% confidence intervals (CI) were computed to measure the strength of association between the dependent and independent variables. A total of 452 patients (242 MDR‐TB and 210 DS‐TB) were included in this study. The mean age of the study participants was 33 years ( SD  ± 14 years). Approximately one‐fifth (78, 17%) of all study participants were human immunodeficiency virus (HIV) positive; 21% (51) of cases and 13% (27) of controls. Risk factors associated with MDR‐TB were a history of previous TB treatment (Adjusted Odds Ratio (AOR): 83.8; 95% CI: 40.7, 172.5), low educational status (AOR: 5.32; 95% CI: 1.43, 19.81); and ages less than 20 years (AOR: 9.01; 95% CI: 2.30, 35.25) and 21–30 years (AOR: 2.61; 95% CI: 1.02, 6.64). HIV infection was also significantly associated with MDR‐TB among new TB patients (AOR: 5.55; 95% CI: 1.17, 26.20). This study shows that clinical and demographic features can be used to indicate higher risks of drug resistance in this setting.